2020
DOI: 10.1523/jneurosci.2665-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Coding of Time-Dependent Frequency Trajectories by Off Responses in Secondary Auditory Cortex

Abstract: Time-dependent frequency trajectories are an inherent feature of many behaviorally relevant sounds, such as species-specific vocalizations. Dynamic frequency trajectories, even in short sounds, often convey meaningful information, which may be used to differentiate sound categories. However, it is not clear what and where neural responses in the auditory cortical pathway are critical for conveying information about behaviorally relevant frequency trajectories, and how these responses change with experience. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 71 publications
5
27
0
Order By: Relevance
“…Traditionally, these behavioural studies were quantified using qualitative “spot checks”, observations without disturbing the nest and cage (of 15 min or lesser), and later studies with short intervals of disturbances to induce pup retrieval or other maternal behaviours. These studies paved the way for more recent optogenetics experiments to perturb neural circuitry and molecular/cellular analysis to determine genes and cell types involved in maternal behaviour (Bendesky et al., 2017; Chen et al., 2019; Chong et al., 2020; Fang et al., 2018; Kohl et al., 2018; Krishnan et al., 2017; Lau, Krishnan, et al., 2020; Lau, Layo, et al., 2020; Li et al., 2019; Maynard et al., 2018; Moffitt et al., 2018; Niv et al., 2015; Tasaka et al., 2018; Wu et al., 2014). However, due to limited person power and/or due to reductionist views to focus on particular behaviours, only certain aspects of the dynamic behaviour were noted and discrete end‐point analysis (such as time to retrieve pups, nesting and errors in retrieval) performed in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, these behavioural studies were quantified using qualitative “spot checks”, observations without disturbing the nest and cage (of 15 min or lesser), and later studies with short intervals of disturbances to induce pup retrieval or other maternal behaviours. These studies paved the way for more recent optogenetics experiments to perturb neural circuitry and molecular/cellular analysis to determine genes and cell types involved in maternal behaviour (Bendesky et al., 2017; Chen et al., 2019; Chong et al., 2020; Fang et al., 2018; Kohl et al., 2018; Krishnan et al., 2017; Lau, Krishnan, et al., 2020; Lau, Layo, et al., 2020; Li et al., 2019; Maynard et al., 2018; Moffitt et al., 2018; Niv et al., 2015; Tasaka et al., 2018; Wu et al., 2014). However, due to limited person power and/or due to reductionist views to focus on particular behaviours, only certain aspects of the dynamic behaviour were noted and discrete end‐point analysis (such as time to retrieve pups, nesting and errors in retrieval) performed in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…Among many acoustic cues, the rising slope of an acoustic stimulus can change the response strength and its latency (Heil 1997a(Heil , b, 2011. In our case, the very sharp rising slope of the adult and pup calls (1-5ms) or subtle variations in the frequency trajectory of the calls (Chong et al 2020) could promote responses even if the neuron CF is far from the spectral content of the vocalizations.…”
Section: The Specificity Of the C57bl/6 Modelmentioning
confidence: 70%
“…Another approach to understand the behavioural role of auditory offset responses could be to study where the AAF is projecting and what could be the use of offset responses in these areas. It was previously shown that offset responses in the secondary auditory cortex are plastic and able to enhance the representation of a newly acquired, behaviourally relevant sound category (Chong et al, 2020). Whether the activity of AAF neurons is crucial for this plasticity to happen remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these quantifications confirm that the neuronal responses measured at sound termination are not affected by the weak and short spectral splatter caused by a fast offset ramp. In the future, the role of offset responses in detecting sound termination should be studied in natural environments, using for example vocalization calls (Chong et al, 2020). This would tell if the auditory system, and the MGB or the AAF more specifically, evolved in a way to meet the challenges of detecting naturally terminating sounds.…”
Section: Discussionmentioning
confidence: 99%